2017
DOI: 10.5606/kbbihtisas.2017.92480
|View full text |Cite
|
Sign up to set email alerts
|

Extracranial head and neck schwannomas: A series of 14 patients

Abstract: Objectives: This study aims to evaluate patients operated due to extracranial head and neck schwannomas. Patients and Methods:A total of 14 patients (6 males, 8 females; mean age 42.6 years; range 7 to 73 years) who were treated for extracranial head and neck schwannomas between January 1995 and December 2015 were retrospectively reviewed. Demographic data, tumor location, surgery, and clinical characteristics of the patients were discussed in light of the literature.Results: All patients were evaluated radiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…[4] Although such tumours may occur at any age, it has been reported that they are most commonly seen between the ages of 20 and 50, with no significant differences in terms of ethnicity or sex. [5][6][7] In the present study, the majority of patients were between the ages of 20-50 years (n=19, 61%) and the peak occurrence in this sample was in the patients' thirties. Therefore, schwannomas should always be included in the differential diagnosis of head and neck masses in both sexes in both middle and old age.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…[4] Although such tumours may occur at any age, it has been reported that they are most commonly seen between the ages of 20 and 50, with no significant differences in terms of ethnicity or sex. [5][6][7] In the present study, the majority of patients were between the ages of 20-50 years (n=19, 61%) and the peak occurrence in this sample was in the patients' thirties. Therefore, schwannomas should always be included in the differential diagnosis of head and neck masses in both sexes in both middle and old age.…”
Section: Discussionmentioning
confidence: 90%
“…On the other hand, since tumours arise from the nerve sheath, even with highly delicate and careful surgery, it is very likely that patients who have no neurological deficit prior to surgery may develop neurological deficits postsurgically. Çakır et al [6] reported a failure rate of 57% in protecting the nerve of origin in their extracranial head and neck schwannoma cases. Therefore, the surgical decision should be informed by an evaluation of the nerve of origin and its likely impact on the patient's quality of life if a postoperative deficit occurs.…”
Section: Discussionmentioning
confidence: 99%